Performance of silver nanoparticles in the catalysis of the oxygen reduction reaction in neutral media: Efficiency limitation due to hydrogen peroxide escape - Neumann, C; Laborda, E; Tschulik, K; Ward, K; Compton, R (2013)
The electrocatalytic activity for oxygen reduction reaction (ORR) at neutral pH of citrate-capped silver nanoparticles (diameter = 18 nm) supported on glassy carbon (GC) is investigated voltammetrically. Novelly, the modification of the substrate by nanoparticles sticking to form a random nanoparticle array and the voltammetric experiments are carried out simultaneously by immersion of the GC electrode in an air-saturated 0.1 M NaClO4 solution (pH = 5.8) containing chemically-synthesized nanoparticles. The experimental voltammograms of the resulting nanoparticle array are simulated with homemade programs according to the two-proton, two-electron reduction of oxygen to hydrogen peroxide where the first electron transfer is rate determining. In the case of silver electrodes, the hydrogen peroxide generated is partially further reduced to water via heterogeneous decomposition. Comparison of the results obtained on a silver macroelectrode and silver nanoparticles indicates that, for the silver nanoparticles and particle coverages (0.035%-0.457%) employed in this study, the ORR electrode kinetics is slower and the production of hydrogen peroxide larger on the glassy carbon-supported nanoparticles than on bulk silver. [Figure not available: see fulltext.] © 2013 Tsinghua University Press and Springer-Verlag Berlin Heidelberg.